2012
DOI: 10.1371/journal.pgen.1003098
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Joint Meta-Analysis of SNP and SNP-by-Smoking Interaction Identifies Novel Loci for Pulmonary Function

Abstract: Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV1), and its ratio to forced vital capacity (FEV1/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV1 and FEV1/FVC across 19 studies (total N = 50,047). We identified three no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 81 publications
5
121
2
Order By: Relevance
“…For example, a meta-analysis of genome-wide studies of respiratory phenotypes, which included gene-smoking interactions, identified multiple functional variants that had been missed in analyses neglecting interaction effects. 49 A secondary methodological study found some evidence for an interaction of smoking with a variant located in the proximity of FMO4 with respect to incident coronary heart disease. 50 These results should motivate secondary analyses of the evergrowing number of (epi)genome-wide data sets of cardiovascular disease, which usually will feature at least crude smoking exposure data, but have neither been compiled nor analyzed with tobacco-related disease in mind.…”
mentioning
confidence: 99%
“…For example, a meta-analysis of genome-wide studies of respiratory phenotypes, which included gene-smoking interactions, identified multiple functional variants that had been missed in analyses neglecting interaction effects. 49 A secondary methodological study found some evidence for an interaction of smoking with a variant located in the proximity of FMO4 with respect to incident coronary heart disease. 50 These results should motivate secondary analyses of the evergrowing number of (epi)genome-wide data sets of cardiovascular disease, which usually will feature at least crude smoking exposure data, but have neither been compiled nor analyzed with tobacco-related disease in mind.…”
mentioning
confidence: 99%
“…One identified a novel variant near MAN2B1 that was associated with percent emphysema on computed tomography (CT) (16) and the other identified two loci that approached genome wide statistical 4 significance for COPD (13). This literature contrasts with that among persons of European ancestry, in whom GWAS have identified multiple loci in genes for lung function and COPD (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) To improve our current understanding of the genetic architecture of lung functionrelated traits in Hispanics/Latinos, we performed a meta-analysis for FEV1, FEV1/FVC, airflow limitation and COPD among six Hispanic/Latino groups in the HCHS/SOL cohort (10,32). Findings were replicated in European, Hispanic and African populations.…”
Section: Examination Of Genetic Risk Among Non-european Populations Mmentioning
confidence: 99%
“…To date, seven meta-analyses of GWAS have now been completed and identified SNP associations with FEV1 and/or FEV1 decline (Hancock et al, 2012;Hancock et al, 2010;Repapi et al, 2010;Soler ArtigasLoth, et al, 2011;Tang et al, 2014;Wain L, 2015).…”
Section: Forced Expiratory Volume In 1 Secondmentioning
confidence: 99%
“…SNPs at the 4q24 locus (Castaldi et al, 2011;Repapi et al, 2010;Soler Artigas, Wain, et al, 2011), SNP rs12604628 in HHIP (Repapi et al, 2010;Soler Artigas, Wain, et al, 2011), rs3995090 in HTR4 (Repapi et al, 2010;Soler Artigas, Wain, et al, 2011) and SNPs in SRY (Sex Determining Region Y)-Box 9 (SOX9) (Hancock et al, 2012;Kim et al, 2014). For SNPs associated with FEV1/FVC and COPD, different SNPs in Transforming Growth Factor, Beta 2 (TGFB2) were identified Soler Artigas, Wain, et al, 2011), rs2869967 in FAM13A (Hancock et al, 2010; J. H. Lee et al, 2014), rs12504628 in HHIP (Repapi et al, 2010;Soler Artigas, Wain, et al, 2011) and different SNPs in HTR4 (Hancock et al, 2010;Soler Artigas, Wain, et al, 2011;Wilk et al, 2012).…”
Section: Genome-wide Association Studies and Meta-analyses In Copdmentioning
confidence: 99%